Pelvis-upper trunk coordination at butterfly stroke and underwater dolphin kick: Application on an elite female butterfly swimmer - Nikodelis, T.; Konstantakos, V.; Kosmadakis, I.; Kollias, I. (Journal of Athletic Enhancement, 2013)
The purpose of the present study was to investigate the modeling of inter-segmental coordination of pelvis-upper trunk segments and its diversification between seemingly similar movements, butterfly and prone/supine dolphin kick, for a specific swimmer, using inertial sensors. Two pairs of 3D accelerometers and gyroscopes were placed at her upper trunk (C7) and pelvis. Segments` flexion - extension angles were analyzed. Peak to peak amplitude values were always larger at the pelvis. Autocorrelations of angles` time histories showed higher periodicity for butterfly (coefficients>0.95 ± 0.05), compared to dolphin kicks (0.7 to 0.9). Angles` power spectrums revealed two fundamental frequencies at the butterfly, around 1 Hz and 2 Hz, accounting for the stroke cycle and the two kicks within it respectively, while dolphin kick tests had one fundamental frequency around 2.2 Hz. Inter-segmental coordination of the pelvis-upper trunk segments had distinct differences between butterfly and dolphin kicks, with a trend to in-phase and to an antiphase coordination mode respectively. Dolphin kicks conditions did not present any exemplar differences between them at all the analyses. This method offers a different view on the coordination of the swimmer`s movement.